Vdiba-based floating lossless inductance simulator employing a single grounded capacitor - Pimpol, Jirapun; Channumsin, Orapin; Thongsopa, Chanchai; Tangsrirat, Worapong (My University, 2016)
This paper presents an actively floating lossless inductance simulator based on employing voltage differencing inverting buffered amplifiers (VDIBAs) as new active components. The proposed synthetic inductor employs only two VDIBAs and one grounded capacitor, which is resistorless structure and suitable for integrated circuit design. The realized equivalent inductance is electronically adjustable through the transconductance parameter of the VDIBA. An application example of the proposed tunable floating lossless inductor on the realization of the second-order RLC bandpass filter has been designed and simulated. PSPICE simulation results with standard 0.35 μm BiCMOS process model are also included to demonstrate the utility as well as the workability of the proposed simulator.
Keywords: Impedance function; Lossless inductance simulator; Voltage differencing inverting buffered amplifier (VDIBA)